Camundongos C57BL/6 infectados com Plasmodium berghei ANKA apresentam diferentes alterações intestinais durante a malária cerebral e não cerebral - Lozano-Trujillo, Laura Alejandra (2022)
Plasmodium infection is one of the parasitic infections with the highest incidence in the world, the most serious complication being cerebral malaria caused by P. falciparum. In addition to brain symptoms, it also causes manifestation in the gastrointestinal system, and the mechanisms that lead to intestinal symptoms are poorly understood. Thus, this study aimed to evaluate possible intestinal alterations in an animal model of cerebral malaria, seeking to understand whether there is a relationship between the development of cerebral malaria and intestinal alterations. C57BL/6 mice were inoculated with Plasmodium berghei ANKAGFP+ and observed for clinical manifestations, intestinal activity and measurement of macro and microscopic characteristics of the intestine, in addition to analyzing the expression of some genes such as ChrgA, Tph-1, Muc-2, VIP, Piezzo-2, Hes-1 and Noch-1. Animals with cerebral malaria showed decreased weight, motility and increased intestinal mucus. Furthermore, it was observed that animals with cerebral malaria showed hyperplasia and hypertrophy of goblet cells, unlike infected animals that did not develop cerebral malaria. On the other hand, infected animals that developed non-cerebral malaria show a decrease in enterochromaffin cells. Also, a decrease in the expression of VIP mRNA was observed in the intestine of animals that developed cerebral malaria. These results suggest that P. berghei ANKA infection affects the intestines differently when animals develop cerebral malaria or not, and that decreased VIP mRNA expression may be involved in the changes in animals that develop cerebral malaria. Keywords: Plasmodium berghei ANKA- Intestine-Goblet Cells-Cerebral Malaria-Enterochromafin Cells.